Seeking Allah, finding Jesus : a devout Muslim encounters Christianity - Qureshi, Nabeel (Grand Rapids, Michigan : Zondervan, 2018)
An unexpected journey from Islam to Christianity. In Seeking Allah, Finding Jesus, Nabeel Qureshi describes his dramatic journey from Islam to Christianity, complete with friendships, investigations, and supernatural dreams along the way. Providing an intimate window into a loving Muslim home, Qureshi shares how he developed a passion for Islam before discovering, almost against his will, evidence that Jesus rose from the dead and claimed to be God. Unable to deny the arguments but not wanting to deny his family, Qureshi's inner turmoil will challenge Christians and Muslims alike. Engaging and thought-provoking, Seeking Allah, Finding Jesus tells a powerful story of the clash between Islam and Christianity in one man's heart -- and of the peace he eventually found in Jesus. - Publisher.
Qureshi describes his dramatic journey from Islam to Christianity, and shares how he developed a passion for Islam before discovering, almost against his will, evidence that Jesus rose from the dead and claimed to be God-- and of the peace he eventually found in Jesus.
pt.1: Called to prayer -- Prayers of my fathers -- A mother's faith -- A community of four -- The perfect book -- Stories of the prophet -- Righteous through ritual prayer -- Diversity in Islam -- The path of Sharia -- Dreams of the faithful -- The month of blessing -- pt. 2: An ambassador for Islam -- Third culture -- Muslims in the West -- Swoons and substitutions -- The father is greater than Jesus -- Heaven's gates and hell's flames -- Treasured traditions -- Signs in the sky -- Honor and authority -- The religion of peace -- pt. 3: Testing the New Testament -- Becoming brothers -- Opening my eyes -- Textual evolution -- Revisiting reliability -- pt. 4: Coming to the crux -- Litmus tests -- Crucifying the swoon theory -- A Muslim at church -- Debating the resurrection -- pt. 5: Jesus: mortal Messiah or divine Son of God -- Genetics and Jesus -- Jesus creates carpenters -- The Divine Son of Man -- Paulemics and the earliest Jesus -- pt. 6: The case for the Gospel -- Tension and Trinity -- Resonating with the Trinity -- Salvation in the balance -- Assessing the Gospel -- pt. 7: The truth about Muhammad -- Muhammad revisited -- The picture-perfect prophet -- Veiling the violence -- Muhammad Rasul Allah? -- pt. 8: The holiness of the Quran -- The case for the Quran -- The Quran, science, and Bucailleism -- Hadith and the history of the Quran -- Those whom their right hands possess -- pt. 9: Faith in doubt -- Rationality and revelation -- The cost of embracing the Cross -- I am near, seek and you shall find -- A field of crosses -- pt. 10: Guided by the hand of God -- Deciphering dreams -- The narrow door -- A stairway out of the mosque -- Time to mourn -- The Word speaks -- Finding Jesus.
Includes bibliographical references (pages 364-370).
Keywords: Qureshi, Nabeel; Christian converts from Islam -- Biography; Autobiographies